NON-OBSERVANCE OF GRICEAN MAXIMS IN TV TALK SHOWS - Risya Nurmeliana Ikhsan, - (2011)
The present study entitled "Non-Observance of Gricean Maxims in TV Talk Shows" investigates the non-observance of conversational maxims in two talk shows: Jakarta Lawyers Club and Kick Andy talk show, and discovers the possible factors affecting the non-observance committed by the speakers in both talk shows. The qualitative-descriptive method is employed. Some descriptive quantification is also employed to examine the trends in the data. The data was collected and then transcribed to be analyzed on the basis of Grice's (1975) theory of Cooperative Principle. It is revealed that the most frequently non-observed maxim is maxim of quantity (51.92%) which is followed by maxim of manner (35.44%), relation (12.09%), and quality (0.55%). The study also finds that four types of maxim non-observance are conducted, i.e. flout, violation, opting out, and infringement. The use of maxim non-observance is apparently influenced by two different factors, namely the time pressure and position of the speakers.